Cellular and molecular insights into incomplete immune recovery in HIV/AIDS patients - Yan, Liting; Xu, Kaiju; Xiao, Qing; Tuo, Lin; Luo, Tingting; Wang, Shuqiang; Yang, Renguo; Zhang, Fujie; Yang, Xingxiang (Frontiers in Immunology, 2023)
Highly active antiretroviral therapy (ART) can effectively inhibit virus replication and restore immune function in most people living with human immunodeficiency virus (HIV). However, an important proportion of patients fail to achieve a satisfactory increase in CD4+ T cell counts. This state is called incomplete immune reconstitution or immunological nonresponse (INR). Patients with INR have an increased risk of clinical progression and higher rates of mortality. Despite widespread attention to INR, the precise mechanisms remain unclear. In this review, we will discuss the alterations in the quantity and quality of CD4+ T as well as multiple immunocytes, changes in soluble molecules and cytokines, and their relationship with INR, aimed to provide cellular and molecular insights into incomplete immune reconstitution.